PIBID from the undergraduates' point of view: possibilities and limits in the development of the program - Helena Maria dos Santos Felício; Claudia Gomes; Luciana Resende Allain (Universidade Federal de Santa Maria, 2014)
This work aims at understanding how the undergraduates, those who take part in the PIBID, analyze the program and its impact on their undergraduate studies and on the University courses. To do so, qualitative and quantitative surveys answered by the 88 participants of the program were applied. The collected data presented: PIBID's contribution to the construction of the participants' pedagogical knowledge, which allows them to see themselves as teachers of a collective group, the school; the idea that the school is an outside field to the teacher's academic training, this being a limitation of the program; and, how fragile the theory-practice relationship is. We can conclude that PIBID gives the students a chance to anticipate their relationship with their future work environment, something considered as important as the subjects they learn in the university.